EFFECT OF SULFUR IN THE REDUCTANTS ON SULFIDATION MECHANISM OF NICKEL LATERITE - Fajar Nurjaman; Yuliana Sari; Anton Sapto Handoko; Fathan Bahfie; Ulin Herlina; Muhammad Miftahurrahman; Dedi Priadi; Deni Ferdian; Bambang Suharno (Indonesian Mining Journal, 2021)
Processing nickel laterite conventionally, namely by pyrometallurgy method, requires high temperature and energy, results in a costive process. Due to its lower temperature reduction process, selective reduction with additives could be an alternative in nickel ore processing. Additives such as sulfur/sulfate have a critical role in promoting the low melting point phase. Sulfur is also found in coal. Therefore, it is important to investigate the effect of sulfur content in reductant on selective reduction of lateritic nickel ore. In this work, the effect of sulfur content (2.68% and 5% S) in anthracite coal as a reductant on selective reduction of limonitic ore was studied clearly. Nickel ore, reductant and sodium sulfate were mixed homogenously and pelletized up to 10-15 mm in diameter. Pellets were reduced using a muffle furnace at 950 to 1150°C for 60 min. Reduced pellets were crushed into -200 mesh before separating the ferronickel and its impurities using a wet magnetic separation process. The result showed that the anthracite coal with 5% S produced concentrate containing 3.56% Ni with 95,97% recovery, which is higher than 2.68% S. The sulfur content in reductant could replace the addition of sulfur/sulfate as the additives in the selective reduction of lateritic nickel ore.